2019
DOI: 10.31234/osf.io/pzbhw
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluating the Evidential Value of Empirically Supported Psychological Treatments (ESTs): A Meta-Scientific Review

Abstract: Empirically supported treatments (or therapies; ESTs) are the gold standard in therapeutic interventions for psychopathology. Based on a set of methodological and statistical criteria, the APA has assigned particular treatment-diagnosis combinations EST status and has further rated their empirical support as Strong, Modest, and/or Controversial. Emerging concerns about the replicability of research findings in clinical psychology highlight the need to critically examine the evidential value of EST research. We… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 0 publications
1
7
0
1
Order By: Relevance
“…For psychotherapy, no recent meta‐analysis fulfilled the inclusion criteria. The quality of studies was found to be low 137 . For pharmacotherapy, the largest meta‐analysis reported a small SMD in comparison with placebo (0.27, see Figure 2) 90 .…”
Section: Resultsmentioning
confidence: 96%
“…For psychotherapy, no recent meta‐analysis fulfilled the inclusion criteria. The quality of studies was found to be low 137 . For pharmacotherapy, the largest meta‐analysis reported a small SMD in comparison with placebo (0.27, see Figure 2) 90 .…”
Section: Resultsmentioning
confidence: 96%
“…Additionally, we asked authors to apply criteria adapted from Southam‐Gerow and Prinstein (2014) to evaluate the evidence base in this special issue. Concerns have been raised regarding the use of such evidence base guidelines because they rely primarily on statistical significance and only require two positive results for favorable evaluation; this is particularly relevant as the dangers of false‐positive findings are increasingly being recognized (e.g., Sakuluk et al, 2019; Tackett et al, 2017). We encourage couple and family intervention researchers to more thoroughly consider issues of replicability (e.g., Tackett et al, 2017) and potential solutions to these problems (e.g., Nosek et al, 2018) as we look to the next decade of research.…”
Section: Future Directionsmentioning
confidence: 99%
“…At the same time, our unrestricted search suggests that replication attempts are rare regardless of trial effect or sample size. A recent investigation (Sakaluk et al, 2019) supports this conclusion, reporting 'weak' evidence for replicability across empirically supported psychotherapies. Unfortunately, a limitation of this study was its classification system, which grouped heterogeneous treatments and treatment comparisons.…”
Section: Discussionmentioning
confidence: 97%